THE LITERATURE REVIEW OF CONSTRUCTION PROJECT SCHEDULING METHODS AND EFFECTIVENESS FOR THE LAST 5 YEARS IN INDONESIA - Rakasyiwi, Gilang Ramadhan; Witjaksana, Budi; Tjendani, Hanie Teki (Transpublika Publisher, 2022)
Resources in the project were definitely limited so planning must be thorough and perfect. To achieve this goal, developers, contractors, and project owners create a project implementation schedule as well as control the implementation of the project itself. Scheduling determines when activities will be started, postponed and completed, so that resource control will be adjusted to the needed that had been determined. In project planning, scheduling was very important in projecting the needed of manpower, materials, and equipment. This study aims to assess project scheduling in general based on literature sources in the form of previous research (journals). The method used in this study was a literature study related to scheduling studies based on construction projects. Data were obtained from several library sources in the form of research journals for the last 5 years related to the research topic. The results showed that each method was complementary, such as LoB combined with CPM or PDM. In scheduling a construction project, a combination of methods needed to be applied to suit the desired construction project.